(untitled) (Research, Society and Development, 2021)
Constitutionally, health is everyone’s right and the State’s duty in Brazil, which highlights its social responsibility to provide health care for the Brazilian population, without any value judgment or discrimination. However, there is a different reality from what is normatively recommended, since social, political and economic inequalities are essential to fundamental rights such as the right to health. Article 14 of the Universal Declaration on Bioethics and Human Rights establishes the principle of Social responsibility and health as essential for the exercise of State actions to promote the exercise of the right to health for the Brazilian population, especially in emergency situations such as the pandemic of COVID. -19. Therefore, the objective was to critically analyze the strategic actions of the Brazilian government in light of the principle of social responsibility and health in view of the COVID-19 pandemic. The proximity of the State with the inviolability of the principle of Social Responsibility and health was observed in the context of the COVID-19 pandemic, based on government actions, policies and determinations instituted by the Brazilian government itself.